Assessment of a feed additive consisting of vitamin B6 (pyridoxine hydrochloride) for all animal species for the renewal of its authorisation (Kaesler Nutrition GmbH). (9th June 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of vitamin B6 (pyridoxine hydrochloride) produced by chemical synthesis as a feed additive for all animal species. The applicant has provided data demonstrating that the additive in the market complies with the conditions of the authorisation. The FEEDAP Panel confirms that the use of pyridoxine hydrochloride under the current authorised conditions of use is safe for the target species, the consumers and the environment. Pyridoxine hydrochloride is non‐irritant to skin and eyes. In the absence of data, no conclusion can be drawn on skin sensitisation potential. Pyridoxine hydrochloride may cause photosensitisation. Despite the lack of data on inhalation toxicity, the additive is not dusty and exposure through inhalation is unlikely. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.